Girls Out Late - Jacqueline Wilson (Corgi Yearling Books, 2000)
Ellie has a boyfriend! Interested in her - not in her best friends, Magda and Nadine! She and Russell are made for each other - drawn together by their shared enjoyment of art. If only Dad thought Russell was perfect too... And as Ellie runs into trouble with a parent who thinks his daughter is too young for after-dark trysts in the park with oh-so-gorgeous Russell, Magda has a crush on a teacher - and Nadine's falling for slimy Liam again. What they need is a girls' night out - Girls Out Late!
Keywords: Relationships -- Relationships; Romance -- Romance